THE LEGAL PHILOSOPHY AND JUSTICE VALUES IN THE ACQUISITION OF LAND RIGHTS IN INDONESIA: A NORMATIVE LEGAL RESEARCH - Widiyono, Tri; Khan, Md Zubair Kasem (International Journal of Law Reconstruction, 2022)
This study aims to describe the authority to control land by the state in various legal and regulatory arrangements from the Basic Agrarian Law, constitution, and other derivative regulations. The object of this study is the various types of land rights that are stated in the various legal arrangements. The method used in this research is normative legal studies that examine legal products with a statutory approach. The findings describe that the 1945 Constitution and the regulations under it regulate how to obtain land rights in order to fulfill the nature and elements of the law. Some of the main things regulated in the legislation are in order to balance the public interest and the sustainability of the national economy. The findings have theoretical implications for regulatory arrangements on aspects that have not been regulated by law. The findings of this study underscore the importance of synchronizing land arrangements at the national level, as well as suggesting harmonization of land laws to avoid overlapping and at the same time accommodate various needs, including public interests, economic development, individual and social interests. Philosophically, this research underscores the aspect of people's prosperity as the most important basis of authority originating from the right to control by the state.